Investigating the impact of diverse PIDs and ESDs in frequency regulation of a wind-diesel hybrid system (2025)
Microgrids are gaining momentum these days as they can generate the cleaner and affordable electrical energy through renewable energy sources. The renewable energy sources such as wind has enough potential however, its operation is restricted as wind speed highly varies over the period of the day and that is why diesel engine generation is a possible solution to overcome the wind challenges as well as to supply the uninterrupted electrical energy to the customers. This paper presents the design of various PID controllers to match the energy generation with load demand and hence to stabilize the operation of the microgrid for various operating conditions. The performance of the PID controllers is obtained through gains calculation, diverse error values and through dynamic responses of the microgrids obtained through diverse controllers. Further, this paper also shows the impact of diverse energy storage devices (ESD) with PID controllers for the microgrid, and it is observed that PIL-PID with redox flow battery outperform other controllers and ESDs and most suited for various working conditions of the microgrid.